1996
DOI: 10.2307/3646297
|View full text |Cite
|
Sign up to set email alerts
|

International Migration and National Development

Abstract: "In this review, we examine theories, data, and research on the macroeconomic relationship between international migration and national development in all world regions. Earlier reviews have generally been pessimistic about the prospects for economic development as a result of international migration. Until recently, however, theories and data have not recognized the complex, multifaceted, and often indirect ways that international migration can influence the economic status of households, communities, and nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
0
5

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(80 citation statements)
references
References 0 publications
2
73
0
5
Order By: Relevance
“…Remittances from internal migrants, although smaller in magnitude, also comprise a vital component of rural livelihoods in many developing countries (Reardon 1997;Rempel and Lobdell 1978). Research shows that remittances relax budget or credit constraints in origin households (Lauby and Stark 1988;Lucas and Stark 1985;Stark and Levhari 1982;Taylor 1999) and provide opportunities for income redistribution and poverty reduction in origin communities or countries (Durand et al 1996a;Durand, Parrado and Massey 1996b;Jones 1998;Rapoport and Docquier 2006;Russell 1986;Taylor et al 1996). To anticipate the macro-level consequences of these flows, we first need to understand the micro-level motives shaping individuals' remittance behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Remittances from internal migrants, although smaller in magnitude, also comprise a vital component of rural livelihoods in many developing countries (Reardon 1997;Rempel and Lobdell 1978). Research shows that remittances relax budget or credit constraints in origin households (Lauby and Stark 1988;Lucas and Stark 1985;Stark and Levhari 1982;Taylor 1999) and provide opportunities for income redistribution and poverty reduction in origin communities or countries (Durand et al 1996a;Durand, Parrado and Massey 1996b;Jones 1998;Rapoport and Docquier 2006;Russell 1986;Taylor et al 1996). To anticipate the macro-level consequences of these flows, we first need to understand the micro-level motives shaping individuals' remittance behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Migrant remittances also serve as a source of income for savings and investment, as confirmed by Taylor [15], and thereby lead to growth and development of an economy. This is corroborated in a study on Mali by Findley and Sow [18], who report that remittances not only covered basic food and cash needs but also allowed people to pay for irrigation in agriculture.…”
Section: Impact Of Remittance Flowmentioning
confidence: 99%
“…Thus, Russell et al [14] concluded that after satisfying subsistence needs, migrant remittances are used for investment purposes such as education, livestock, farming, and small scale enterprise. Taylor [15] has also argued that remittances have multiplier effects that work to increase national income. In a study on Senegal, Diatta and Mbow [16] found that remittances were a substantial source of revenue for families with migrant members and were also used to promote development in migrants' home communities.…”
Section: Impact Of Remittance Flowmentioning
confidence: 99%
“…Such studies conclude that remitt ances are not put into productive use and instead, they are conspicuously consumed (Chami et al, 2003;Taylor et al, 1996;Durand and Massey, 1992;and Papademetrious and Martin, 1991). It is possible that this research on remitt ance use off ers a partial and possibly distorted view of how remitt ances infl uence demand, due to the assumed fungibility of income.…”
Section: Remitt Ances and Expenditures In Rural Householdsmentioning
confidence: 99%